تعدّد الزوجات بين الحقّ والرّخصة في التشريعات الأسريّة المغاربية - بوعلالة, عمر (جامعة الوادي University of Eloued, 2015)
يثور الخلاف في التشريعات الأسرية المغاربية في حكم التعدّد أو تكييفه القانوني: فهل هو رخصة لا يجوز اللّجوء إليها إلا إذا توافر موجبها؟ أم هو حقّ يكون للشّخص أن يستعمله دون قيد أو شرط إلاّ القيود التي قرّرها الشّرع؟ وبالرّجوع إلى الشّريعة الإسلاميّة نجدها منحت الرّجل حقّ الزواج بأربع نسوة، ولم تقيّده في ذلك إلا بالعدل بينهن. وهذا يعني أن فرض قيود أخرى على التعدّد عن طريق التشريع، أو وضع عقوبات تحول دون حقّ الرّجل بالزواج بأكثر من زوجة، لا يمكن أن يفهم إلا ّأنّه تطاول على الشّرع؛ بتحريم ما أحلّه الله. وخلاصة النّظر في هذه المسألة كما عالجتها التّشريعات ورصدها البحث التمييز بين اتجاهين: اتجاه يرى تقييد تعدّد الزوجات بتضييق إعماله؛ أي يجعله من قبيل الرّخصة التي لا يجوز استعماله إلاّ إذا توافر موجبها. ويعني ذلك أن التعدّد ليس حقّا للرجل وليس أصلا من أصول الشّريعة بل هو استثناء من القاعدة، لابدّ اخضاعه لرقابة القاضي. واتجاه ذهب إلى منع تعدّد الزوجات منعا مطلقا، بل اعتبره جريمة يعاقب عنها القانون. Abstract: Polygamy between right and permission in Maghreb family legislation Disagreement arises in legislation in the Maghreb family about pluralism whether it is permitted and not be resorted to only if the availability is afforded? Or is it the right of a person that is used without restriction or condition, but only the restrictions established the islamic law. The Islamic Sharia law has granted man the right to marry four women with no restrictions only justice among them. And this means the imposition of other restrictions concerning polygamy through legislation or impose sanctions to prevent the man's right to marry more than one wife, cannot be understood as an insult to the islamic law by prohibiting what Allah permitted. To summary of the issue, as dealt with by the legislations and exposed by the research combines The distinction between two opinions: The first considers restriction as a kind of permission, used only if the If positive availability is afforded, which means, this is not really that the poligamy to men is not a right and not originally from the assets of the sharia, but is an exception to the rule which should be subject to control by the judge. The second prevents polygamy considering it as a crime punishable by the law.
Keywords: الزواج؛ تعدّد الزوجات؛ التشريعات الأسريّة؛ الرخصة؛ حقّ الرجل؛ الزوجة